Survey and analysis on oral microbial profile of Dhaka city dwellers and their association with different diseases in the community - Anamika, Mahmuda Khatun; Zohra, Fatima Tuj (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Biotechnology, 2023.